The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.18295/squmj.2016.16.03.003
|View full text |Cite|
|
Sign up to set email alerts
|

Currently Available Tools and Teaching Strategies for the Interprofessional Education of Students in Health Professions: Literature review

Abstract: Interprofessional education (IPE) is designed to provide students from different health sectors with opportunities to work together to enhance future collaboration. The implementation of IPE activities is a current trend in various countries. This review exclusively targets IPE issues involving undergraduate health profession students and highlights various approaches in different regions. A total of 28 articles published in peer-reviewed journals between January 2012 and July 2015 were assessed to determine r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 43 publications
0
39
0
4
Order By: Relevance
“…Although there remains no universally agreed upon best methodology for teaching interprofessional skills, a recently published review of 28 educational programs found nine major education strategies currently available for the implementation of IPE, with community and rural clinical rotations being among the most commonly used [6]. Studies of interprofessional clinical rotations in community and rural settings show that these experiences increase students’ confidence in caring for underserved populations and affect long-term changes in practice behavior through the modification of attitudes, values and competencies [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there remains no universally agreed upon best methodology for teaching interprofessional skills, a recently published review of 28 educational programs found nine major education strategies currently available for the implementation of IPE, with community and rural clinical rotations being among the most commonly used [6]. Studies of interprofessional clinical rotations in community and rural settings show that these experiences increase students’ confidence in caring for underserved populations and affect long-term changes in practice behavior through the modification of attitudes, values and competencies [6].…”
Section: Introductionmentioning
confidence: 99%
“…Studies of interprofessional clinical rotations in community and rural settings show that these experiences increase students’ confidence in caring for underserved populations and affect long-term changes in practice behavior through the modification of attitudes, values and competencies [6]. While many clinical programs have been established in the US and internationally, few clinical rotations include global health experiences where the students spend time abroad participating in intentionally-directed interprofessional training.…”
Section: Introductionmentioning
confidence: 99%
“…[20] IPE activities, such as simulation-based education programs, patient-centered case studies, health promotion activities and interactive lectures, are proved to be strategies for developing and strengthening interprofessional competencies. [21] In addition, educators are also recommended to develop curricula that can provide medical students of different majors with opportunities to learn from each other, since those curricula not only enhance their collaboration and teamwork skills, but also support them to know other professionals' roles and responsibilities, and thus improve patient outcomes.…”
Section: Enhancing Mutual Understandingmentioning
confidence: 99%
“…[ 1 ] This allows learners to approach clinical scenarios with more confidence, creating an atmosphere that puts patients at ease, improves patient safety, and decreases medical errors. [ 2 ] Most medical students make the transition from the classroom to clinical settings in their third year of training; simulations may facilitate bridging that transition if students can get exposure and practice concepts in the year prior to their first interactions with patients.…”
Section: Introductionmentioning
confidence: 99%